2009
DOI: 10.1097/eja.0b013e3283232c69
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of prolonged mechanical ventilation in a cohort of 5123 cardiac surgical patients

Abstract: This review allowed us to assess predictors, helping us to identify 'a priori' patients more likely to undergo PMV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
113
5
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(145 citation statements)
references
References 29 publications
18
113
5
9
Order By: Relevance
“…As pointed out by Doering et al [23], some preoperative factors may influence postoperative factors also correlated with prolonged length of stay in the ICU. Thus, correlation between prolonged MV and higher age [12], females [12], diabetes [24], hypertension [24], LVEF <30% [24], chronic RF [24] and BMI <20 [25] have been observed. The prolonged MV also correlates with surgical factors such as aortic clamping [24], cardiopulmonary bypass time >120 minutes [25] and other postoperative factors such as RF [25].…”
Section: Bmi -Body Mass Index; Ef -Ejection Fraction; Oi-sc -Oxygenatmentioning
confidence: 99%
“…As pointed out by Doering et al [23], some preoperative factors may influence postoperative factors also correlated with prolonged length of stay in the ICU. Thus, correlation between prolonged MV and higher age [12], females [12], diabetes [24], hypertension [24], LVEF <30% [24], chronic RF [24] and BMI <20 [25] have been observed. The prolonged MV also correlates with surgical factors such as aortic clamping [24], cardiopulmonary bypass time >120 minutes [25] and other postoperative factors such as RF [25].…”
Section: Bmi -Body Mass Index; Ef -Ejection Fraction; Oi-sc -Oxygenatmentioning
confidence: 99%
“…It has been shown that patients with preexisting low ejection fraction (EF) are at a higher risk of developing respiratory problems than patients with normal EF (11,12,(32)(33)(34)(35)(36). Impaired left ventricular ejection fraction (LVEF) of less than 30%, history of previous myocardial infarction (36,37), and preexisting congestive heart failure, age, diabetes mellitus and arterial hypertension, have all been shown to be independent, significant predictors for developing these respiratory problems (30,31,35). Low EF especially, has a determining role in patients with a preexisting cardiac problem, mainly valvular heart diseases, such as low gradient aortic stenosis (AS).…”
Section: Underlying Function Of the Left Ventriclementioning
confidence: 99%
“…It is also, considered to be a major risk factor for patients undergoing CABG, which could predict the possibility of postoperative mortality and morbidity in these patients, especially for diabetic patients with respiratory problems (30)(31)(32)(33)(34)(35)(36)(37)(38). On the other hand, there is a great amount of current evidence that demonstrates a very clear difference between, well controlled and poorly controlled diabetes mellitus, in predicting respiratory problems, hence, controlling the level of blood glucose in diabetics (at least below 200 mg/dL blood levels) would greatly affect the overall clinical outcome, including respiratory outcomes, in patients undergoing cardiac surgery, especially CABG, compared with poorly controlled diabetics (35)(36)(37).…”
Section: Preexisting Endocrine Disordersmentioning
confidence: 99%
“…Some authors in their studies refer alternatively to preoperative, intraoperative and immediately postoperative parameters, others showed that hemodynamic status on ICU admission and early postoperative events were more important than intraoperative variables, to predict ventilatory dependence, defined as MV greater than 72 hours after cardiac surgery (Cislaghi et al, 2009;Rajakaruna et al, 2005).…”
Section: Timing Of the Tracheotomymentioning
confidence: 99%